2018
DOI: 10.1111/jasp.12565
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of intergroup contact with former adversary are linked to distinct reconciliatory acts through symbolic and realistic threat

Abstract: In a society burdened with the most severe type of intergroup conflict, we examined the association between willingness to reconcile with former adversary, intergroup contact with, and perceived threat from former adversary. We focused on three reconciliatory acts—forgiveness to the outgroup, support for ingroup apology and support for financial compensation to the outgroup. We included different forms of positive and negative intergroup contact—direct and indirect (extended and mass‐mediated). In the link bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 65 publications
(108 reference statements)
3
45
2
Order By: Relevance
“…Secondary transfer effects of positive direct contact have mostly been demonstrated in cross‐sectional research (Pettigrew, 2009) with only a few studies using longitudinal (Eller & Abrams, 2004; Mähönen & Jasinskaja‐Lahti, 2016; Tausch et al., 2010; Van Laar et al., 2005) or experimental designs (e.g., Shook et al., 2016; Spiegler et al., 2021). Secondary transfer effects have also been found for other types of intergroup contact—extended (e.g., Joyce & Harwood, 2014), mass‐mediated (e.g., Rupar et al., 2021a), or imagined contact (e.g., de Carvalho‐Freitas & Stathi, 2017; Harwood et al., 2011; Visintin, Birtel, et al., 2017), and for a variety of outcome measures including behavioral intentions (Meleady & Forder, 2019) and actual behavior (Zingora & Graf, 2019). In addition, secondary transfer effects have been found among children and adolescents (e.g., Vezzali et al., 2018; Vezzali & Giovannini, 2012), student samples (e.g., Shook et al., 2016), and adults (e.g., Tausch et al., 2010), and they have been documented not only for ethnic majority but also minority groups (e.g., Bowman & Griffin, 2012; Marrow et al., 2019, for a recent review on secondary transfer effects see Vezzali et al., 2021).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Secondary transfer effects of positive direct contact have mostly been demonstrated in cross‐sectional research (Pettigrew, 2009) with only a few studies using longitudinal (Eller & Abrams, 2004; Mähönen & Jasinskaja‐Lahti, 2016; Tausch et al., 2010; Van Laar et al., 2005) or experimental designs (e.g., Shook et al., 2016; Spiegler et al., 2021). Secondary transfer effects have also been found for other types of intergroup contact—extended (e.g., Joyce & Harwood, 2014), mass‐mediated (e.g., Rupar et al., 2021a), or imagined contact (e.g., de Carvalho‐Freitas & Stathi, 2017; Harwood et al., 2011; Visintin, Birtel, et al., 2017), and for a variety of outcome measures including behavioral intentions (Meleady & Forder, 2019) and actual behavior (Zingora & Graf, 2019). In addition, secondary transfer effects have been found among children and adolescents (e.g., Vezzali et al., 2018; Vezzali & Giovannini, 2012), student samples (e.g., Shook et al., 2016), and adults (e.g., Tausch et al., 2010), and they have been documented not only for ethnic majority but also minority groups (e.g., Bowman & Griffin, 2012; Marrow et al., 2019, for a recent review on secondary transfer effects see Vezzali et al., 2021).…”
Section: Introductionmentioning
confidence: 92%
“…Relatedly, greater outgroup morality (perceiving the outgroup as honest, trustworthy, and sincere) also explains the effect of positive intergroup contact on outgroup attitudes (Brambilla et al., 2013; Vezzali et al., 2019). Finally, there is evidence that trust and outgroup morality generalize to other secondary outgroups consequently improving attitudes towards them (e.g., trust: Rupar et al., 2021a; Žeželj et al., 2020; outgroup morality: Vezzali et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true when considering that the relation between positive and negative contact forms can be more complex than expected and positive and negative direct and indirect contact can interact in several ways (Árnadóttir et al., 2018; Schäfer et al., 2021). Finally, Rupar and Graf (2019) found that negative mass‐mediated contact was positively associated with negative affect (i.e., intergroup threat).…”
Section: Existing and Emerging Forms Of Indirect Contactmentioning
confidence: 99%